Barreiras para a implementação de práticas docentes com uso das Tecnologias de Informação e Comunicação nos anos iniciais do ensino fundamental - Uehara, Flavia Maria (Universidade Federal de São Carlos, 2018)
If we consider that Information and Communication Technology (ICT) can be an aiding tool in the teaching and learning process, it is important to investigate the existence of adequate and available resources, how much the teachers are prepared to use them and how they incorporate that into classroom planning. In order to understand these questions, this research quest to identify the barriers faced by teachers in the use of ICT in a public school during the development of activities with Learning Objects in computer labs with students from the first years of elementary school. The methodological approach used was the Case Study and the research was carried out a county school located in the countryside of the State of São Paulo. We used as data collection sources: the computer lab activities book records; observation diary with notes held in the computer lab; questionnaires applied to ten teachers; interviews with seven teachers; and observations during intervention activity proposed to the school's teachers. The results indicate that, in technical terms, teachers are prepared to use ICT in classroom with their students. However, in pedagogical, management, and structural terms there is still the need to invest in public policies and actions so that teachers can prepare lessons that can take advantage of all the potential of these resources. We also identified the shortage of Learning Objects appropriate to this educational stage and the requirement of investments in the production of this type of resource.
Keywords: Tecnologias de Informação e Comunicação; Barreiras; Objetos de Aprendizagem; Laboratório de Informática; Prática docente; Information and Communication Technology; Barriers; Learning Objects; Computer lab; Teaching practice; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO